Kepemilikan Institusional, Kepemilikan Asing dan Pengungkapan Corporate Social Responsibility - Mahadewi, Ida Ayu Sinta; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p02, 2023)
This study aims to examine the effect of institutional ownership and foreign ownership on CSR disclosure. Communicating CSR information can be done by disclosing CSR. The research was conducted at service companies in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange (IDX). The research population is 67 companies. Determining the number of samples using purposive sampling technique with three criteria and then obtained 32 samples. Data were analyzed using multiple linear regression analysis. The results show that institutional ownership has a positive effect on CSR disclosure, while foreign ownership has a negative effect on CSR disclosure. The results of this study can theoretically confirm agency theory and corporate governance. Keywords: Corporate Social Responsibility; Institutional Ownership; Foreign Ownership